The Effect of Classical Guidance Using the “Self Dev” Podcast Media on the Self-Confidence of Grade XI Students at SMA Negeri 18 Medan - Yemima Nathania Sayna; Rafael Lisinus Ginting (Era Scientific Publisher, 2025)
Self-confidence is an essential aspect of adolescent development; however, most students at SMA Negeri 18 Medan are still categorized as having a moderate level of self-confidence. Classical guidance services can help enhance students’ self-confidence, yet conventional media are often perceived as less engaging by students. Therefore, this study employed the “Self Dev” podcast as an alternative medium that is interactive and easily accessible. The aims of this study were to describe students’ self-confidence and to examine the effect of classical guidance services using podcast media on students’ self-confidence. The research method used was a quasi-experimental design with a Control Group with Active Intervention. The research population consisted of 175 students, while the sample was selected using purposive sampling, involving 70 students divided into an experimental group and a control group. The research instrument was a self-confidence questionnaire covering four aspects: belief in one’s own abilities, courage in facing challenges, self-acceptance, and feelings of being worthy of appreciation, adapted from Alkhaldi et al. (2021). Of the 50 questionnaire items, 39 were declared valid; after a re-validation process, 30 items were retained with high reliability (Cronbach’s Alpha = 0.896). The prerequisite analysis indicated that the data were normally distributed and had homogeneous variances. The results of the independent samples t-test showed a significant increase in self-confidence in the experimental group compared to the control group (p = 0.048; mean difference = 2.342). Thus, it can be concluded that classical guidance using the Self Dev podcast by Andreas Bordes is effective in improving students’ self-confidence.